PERANCANGAN SISTEM INFORMASI PENDATAAN PEMAKAIAN BAHAN BAKAR KENDARAAN PADA PT.DAHEPA DAMAI PRATAMA DENGAN MENGGUNAKAN BAHASA PEMROGRAMAN VISUAL BASIC.NET DAN DATABASE SQL SERVER - Leonard Tambunan; Karolina Talia Sela (Jaringan Sistem Informasi Robotik-JSR, 2018)
PT. Dahepa Damai Pratama is a company who working construction engineering & transportation services. In the process of processing Data collection of vehicles Fuel Consumption is still using Microsoft Excel applications, Microsoft Word in terms of recording or inputting data so it takes a long time in performing their duties and responsibilities respectively This research carry out to develop data processing Data collection of vehicles Fuel Consumption system and make it easier. PT. Dahepa Damai Pratama need a new data processing information system by utilizing the computer system who support the application system Visual Basic and SQL Server. With this Visual Basic programming and SQL Server Database in Data collection of vehicles Fuel Consumption can help to entry data and reported